The effectiveness of the ERP program in raising the efficiency of supply management – A field study on King Saud medical city in Riyadh – - Sharahily, Fahd Hassan Ali; Al-Shammari, Wael Shafi (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study aims to demonstrate the effectiveness of the ERP resource program in raising the efficiency of supply management at King Saud Medical City in Riyadh. This is in light of the high demand witnessed for a resource planning program and system by medical institutions in Saudi Arabia. To achieve the main objective of this study, the researcher adopted the descriptive and analytical approach as an approach to preparing the study. In addition to the use of the questionnaire as a main tool for collecting data from the members of the study population, who number (85) employees of the users of (ERP Resources Program) in the Supply Department in King Saud Medical City in Riyadh. Following the collection and analysis of data from the study community, a set of results were reached, the most prominent of which are: Emphasizing the existence of a positive statistically significant relationship between (ERP Resource Program) in its various roles (achieving compatibility and effectiveness, managing and planning medical stocks, effective control) in King Saud Medical City, And the degree of improvement in the efficiency of the dimensions of supply management (economic cost, response and cooperation) in King Saud Medical City in Riyadh, where the value of the correlation coefficient was 0.996. In light of the results reached, several recommendations were suggested, the most important of which are: the need to enhancing the best use of the ERP system in reducing storage costs within the departments and departments of King Saud Medical City. The maximum benefit from the ERP system must be made to accelerate the decision-making process within King Saud Medical City in Riyadh.
Keywords: King Saud Medical City; ERP resources program; supply management; medical inventory management; hospital supervision